Clinical evaluation of a new pressure ulcer risk assessment instrument, the Pressure Ulcer Risk Primary or Secondary Evaluation Tool (PURPOSE T). (28th September 2017) - Coleman, Susanne; Smith, Isabelle L.; McGinnis, Elizabeth; Keen, Justin; Muir, Delia; Wilson, Lyn; Stubbs, Nikki; Dealey, Carol; Brown, Sarah; Nelson, E. Andrea; Nixon, Jane
Abstract: Aim: To test the psychometric properties and clinical usability of a new Pressure Ulcer Risk Assessment Instrument including inter‐rater and test–retest reliability, convergent validity and data completeness. Background: Methodological and practical limitations associated with traditional Pressure Ulcer Risk Assessment Instruments, prompted a programme to work to develop a new instrument, as part of the National Institute for Health Research funded, Pressure UlceR Programme Of reSEarch (RP‐PG‐0407‐10056). Design: Observational field test. Method: For this clinical evaluation 230 patients were purposefully sampled across four broad levels of pressure ulcer risk with representation from four secondary care and four community NHS Trusts in England. Blinded and simultaneous paired (ward/community nurse and expert nurse) PURPOSE‐T assessments were undertaken. Follow‐up retest was undertaken by the expert nurse. Field notes of PURPOSE‐T use were collected. Data were collected October 2012–January 2013. Results: The clinical evaluation demonstrated "very good" (kappa) inter‐rater and test–retest agreement for PURPOSE‐T assessment decision overall. The percentage agreement for "problem/no problem" was over 75% for the main risk factors. Convergent validity demonstrated moderate to high associations with other measures of similar constructs. Conclusion: The PURPOSE‐T evaluation facilitated the initial validation and clinical usability of the instrument and demonstrated that PURPOSE‐T is suitable of use in clinical practice. Further study is needed to evaluate the impact of using the instrument on care processes and outcomes.